Coinfection with Rickettsia helvetica and Herpes Simplex Virus 2 in a Young Woman with Meningoencephalitis. (19th October 2011) - Nilsson, Kenneth; Wallménius, Katarina; Påhlson, Carl
Abstract : Herpes virus type 2 DNA was detected by PCR in the cerebrospinal fluid in a young woman presenting with headache, stiff neck and pleocytosis, and serological findings consistent with reactivation. Since she was exposed to ticks, Lyme disease and tick-borne encephalitis were excluded. Further investigation in an ongoing project, using PCR and sequencing of the amplified products, showed the presence of Rickettsia helvetica in the cerebrospinal fluid. The bacteria were also isolated in Vero cell culture, and microimmunofluorescence confirmed the development of antibodies against Rickettsia spp. with predominance of IgM reactivity consistent with recent infection. She was treated with antibiotics and improved rapidly. The patient could easily have been judged to have isolated herpes meningitis. Because Sweden and other European countries are endemic areas for rickettsioses, the paper reaffirms the importance of investigating for the presence of rickettsial infections in endemic areas in cases of meningitis of uncertain aetiology.